Characteristics of Malaysian, Sulawesian and Brazilian Cocoa Butters, Their Blends and Chocolate - Abdul Hamid, Mansoor (1997)
This study was conducted with three fold objectives, (i) to determine the physico-chemical and sensory characteristics of cocoa butter commercially produced by grinders in Malaysia with Sulawesian and Brazilian cocoa butter were used as a comparison, (ii) to determine the physico-chemical characteristics of blended cocoa butter and (iii) to determine the compatibility and acceptability of the chocolate quality made therefrom. Static crystallization for Malaysian and Sulawesian cocoa butter was found not to be significantly different (P>0.05); however they were significantly different (P<0.05) from that of the Brazilian cocoa butter. The same observation was made on the melting behaviour and the percent of solid fat content.Iodine values (I.V) of all Malaysian and Sulawesian cocoa butter (34.75-36.15) were not significantly different (P>0.05) but they were significantly lower (P<0.05) than that of Brazilian cocoa butter (40.31). The free fatty acids (FFAs) for all samples were in the standard range «l.75%) except for the sample from Brazil and two samples from Malaysia . All cocoa butter samples had saponification value (S.V) in the standard range (188 -198); however S.V for the Brazilian cocoa butter samples (193.57) was significantly higher (P<0.05) than other samples. All samples have unsaponifiable matter (USM) within the standard range «0.35%) except for the Brazilian cocoa butter sample. Only Malaysian II sample had the Peroxide Value (p.V) within the standrad range «4.0). The study found that there was no significant difference (P>0.05) in the refractive index (R.I) among all samples. All the values were within the standard range. The fatty acid compositions (FAC) of Malaysian and Sulawesian cocoa butter samples were not significantly different (P>0.05); however, both were significantly different (P<0.05) from the Brazilian sample There was no significant difference (P>0.05) in triglyceride composition for all Malaysian cocoa butter samples. There was a significant difference (P<0.05) in the content of PliO, PLiP, POP and SOA between Malaysian and Sulawesian cocoa butter. The triglyceride composition of the Brazilian cocoa butter sample was significantly different (P<0.05) from the two samples. All the samples contained many flavour descriptives which were objectionable to the panelist. The Malaysian, Sulawesian and their blended cocoa butter showed the same melting profile and hardness. The melting behaviour and hardness of Brazilian cocoa butter, and its mixture with either Malaysian or Sulawesian cocoa butter were affected more by the amount of Brazilian cocoa butter in the blend. Increasing the Brazilian cocoa butter by 20% has significantly (P<0.05) decreased the melting point, enthalphy and the hardness values. Based on the physico-chemical characteristics, 40% of Brazilian cocoa butter was the minimum level accepted to be incorporated in a good quality blended cocoa butter. Good quality chocolates were obtained from a blend containing 60% of Malaysian cocoa butter and 40% of Brazilian cocoa butter. This findings were based on the chocolate resistance to bloom, glossiness, hardness and sensory evaluation.